1985
DOI: 10.1111/j.1600-9657.1985.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of a sonic vibratory endodontic instrument

Abstract: Frasca P. Effectiveness and safety of a sonic vibratory endodontic instrument. Endod Dent Traumatol 1985; 1: 69-76.Abstract -An air-driven sonic vibratory handpiece to which specially designed K-type fifes are attached has been developed. When activated, the root canal instruments will vibrate in a whirling motion, and when moved up and down, will abrade the root canal wall. The sonic system was tested in simulated root canals in plastic blocks and in usage tests iu dogs' teeth. Fortynine roots in 3 dogs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 22 publications
1
32
0
4
Order By: Relevance
“…Sonic instruments for endodontics were first reported by Tronstad et al, [19]. Sonic irrigation operates at a lower frequency (1-6 kHz) and produces smaller shear stresses than ultrasonic irrigation Ahmed of air entrapment, when the needle tips are placed too far away from the apical end of the canals.…”
Section: Sonic Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonic instruments for endodontics were first reported by Tronstad et al, [19]. Sonic irrigation operates at a lower frequency (1-6 kHz) and produces smaller shear stresses than ultrasonic irrigation Ahmed of air entrapment, when the needle tips are placed too far away from the apical end of the canals.…”
Section: Sonic Irrigationmentioning
confidence: 99%
“…This highly flexible microbrush is molded entirely from polypropylene and might be used manually with a rotary action. Weise et al, showed that debris was effectively removed from simulated canal extensions and irregularities with the use of the small and flexible CanalBrush with an irrigant [19].…”
Section: B) Mechanical Agitation Techniques 1 Rotary Brushmentioning
confidence: 99%
“…Tronstad et al (11) found longitudinal parallel grooves on the canal walls that had been apparently caused by the tips of the files. Walmsley et al (12) found that during the process of ultrasonic instrumentation, a distinct pattern or marking was left in the dentin of the canal walls and that the longitudinal marks suggested the file tip may have been working as a hand file and not oscillating properly.…”
mentioning
confidence: 98%
“…Tronstad ve ark. 35 sonik aletlerle birlikte EDTA ve NaOCl solüsyonunun kullanılmasının etkinliklerini değerlendirmişler ve sonik aletlerle EDTA solüs-yonu kullanımının, daha etkili olduğunu belirtmişlerdir.…”
Section: Sonik Sistemlerunclassified